Influence Green Product, Green Price and Green Promotion Against Consumer Purchase Intention with Brand Awareness As Moderation on Commonsense Market - Ni Putu Crosita Vitri Ardiani; Ida Ayu Iswari Pidada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines public awareness of environmental issues and the use of environmentally friendly products. Currently, companies selling environmentally friendly products still face challenges in attracting consumer purchasing interest. Therefore, this study aims to analyze the influence of Green Product, Green Price, and Green Promotion on Purchase Intention with Brand Awareness as a moderating variable in Commonsense Market consumers. This study uses a quantitative approach. Data collection was carried out by distributing online questionnaires to 170 Balinese people and the data obtained were analyzed using SEM-PLS. The results showed that Green Product, Green Price, and Green Promotion had a positive and significant effect on Purchase Intention, but Brand Awareness moderation produced mixed results with evidence that it strengthened the influence of Green Product on Purchase Intention, weakened the influence of Green Price on Purchase Intention, and theoretically was able to strengthen the influence of Green Promotion on Purchase Intention but was not statistically significant.